THE ROLE OF PERSONAL RESOURCES ON LECTURERS WORK ENGAGEMENT - Sutarno; Suprayitno (jfpublisher, 2023)
Job demand is the moderating variable that influences the job resources and personal resources on work engagement. Work engagement is a condition in completing the work related to a state of mind which is characterized by vigor, dedication, and absorption. The level of work engagement is calculated based on vigor, dedication, and absorption indicators. This research aims to analyze the effect of personal resources on lecturers’ work engagement based on the Job Demands-Resources Theory. The results of this research are expected in identifying factors that influence the lecturers’ work engagement considering that work engagement has been identified as a determinant of employee turnover rates. The increased work engagement is expected to reduce the turnover rate of lecturers, especially for young lecturers. Based on the purposive sampling technique, the samples used in this research were 33 lecturers on Universitas Slamet Riyadi. This study uses personal resources of hardiness as main variables with commitment, control, and challenges as independent variables. Besides that, this research also uses work engagement as main variable with vigor, dedication, and absorption as dependent variable. The results of this research found that the effect of challenge on vigor, commitment to dedication, commitment to vigor, and control on dedication was significant. While the effect of challenge on absorption, challenge on dedication, commitment to absorption, control of absorption, and control of vigor has no significant effect.